Green Prospective Teachers: A Research on Prospective Teachers' Sustainable Environmental Behaviors, Consumption Habits and Ecological Footprint Awareness - Arslan, Ayten; Durmus, Esen (Sage Publications Inc, 2025)
The aim of the study is to reveal the relationships between prospective teachers' awareness of reducing ecological footprint, their sustainable consumption behaviours and their behaviours towards sustainable environmental education by using Structural Equation Modelling (SEM). In the study, a cross-sectional survey model was adopted, and the sample consisted of 533 prospective teachers studying in Science, Preschool, Primary School and Social Studies Teacher Education programmes of state universities located in three different provinces in eastern T & uuml;rkiye. As a result of the data analysis, it was determined that there was a moderate positive relationship between ecological footprint awareness and sustainable consumption behaviour, a moderate positive relationship between ecological footprint awareness and behaviour towards sustainable environmental education, and a high positive relationship between sustainable consumption behaviour and behaviour towards sustainable environmental education. SEM results show that awareness towards reducing ecological footprint has a weak but significant indirect effect on behaviour towards sustainable environmental education and sustainable consumption behaviour plays a partial mediating role in this effect. In addition, the total effect of awareness towards reducing ecological footprint on behaviour towards sustainable environmental education was found to be positive and statistically significant. In addition, awareness towards reducing the ecological footprint explains 85% of sustainable consumption behaviour. Together with sustainable consumption behaviour, awareness towards reducing ecological footprint explains 14.6% of the behaviour towards sustainable environmental education. These results indicate that increasing prospective teachers' awareness of the ecological footprint can play an important role in improving their sustainable consumption behaviours and their behaviours towards sustainable environmental education.
Keywords: sustainable environmental behaviour; sustainable consumption behaviour; ecological footprint awareness; structural equation modelling; prospective teachers